New materials for our industries: Pangium Edule Reinw(Kepayang) - Any takers for development of products? - Universiti Putra Malaysia, Research Management Centre (Research Management Centre, Universiti Putra Malaysia, 2007)
Pangium edute Reinw. or locally known as 'kepayang, pangi or keluak', is monotypic and belongs to the family Flacourtiaceae (figure I). They can reach heights of up to 40m. and is found in the wild or is more commonly cultivated especially in villages in Sabah and Sarawak.The boles are straight and often reach a diameter of I m. kepayang offers good timber source to the locals.The seeds contain high quality oil which has been used for cooking for decades even in areas where coconut is plentiful. The investigation into P. edule was initiated following the observation of the wide use of its seeds as a preservative for meat and fish throughout the Dusun community in Sabah, and the widely used oil from the seeds for cooking in Sarawak.